Pengaruh Gaya Hidup, Religiusitas, Impulsif Buying, Hedonisme, dan Harga Terhadap Keputusan Pembelian Di Online Store Media Sosial Dengan Self Control Sebagai Variabel Intervening - Intan Ayu (Al-Musthofa: Journal of Sharia Economics, 2019)
This study uses quantitative research, the aim is to determine the influence of lifestyle, religiosity, impulsive buying, hedonism and price on purchasing decisions in social media online stores with self-control as an intervening variable. The sample used in this study was 60 students from the undergraduate student population of Islamic Economics UIN Sunan Ampel and S1 Islamic Economics UNAIR Surabaya. The analysis used in this study is Partial Least Square (PLS) with the smartPLS 3.0 application. The results of this study indicate that religiosity, impulsive buying, hedonism have a positive effect on purchasing decisions. Meanwhile, self-control, lifestyle and prices have a negative effect on purchasing decisions. Furthermore, the variables of religiosity, impulsive buying, hedonism and price have a positive effect on self-control. Meanwhile, lifestyle variables have a negative effect.